Money, liquidity, and monetary policy - Tobias Adrian; Hyun Song Shin (Federal Reserve Bank of New York, 2009)
In a market-based financial system, banking and capital market developments are inseparable, and funding conditions are closely tied to fluctuations in the leverage of market-based financial intermediaries. Offering a window on liquidity, the balance sheet growth of broker-dealers provides a sense of the availability of credit. Contractions of broker-dealer balance sheets have tended to precede declines in real economic growth, even before the current turmoil. For this reason, balance sheet quantities of market-based financial intermediaries are important macroeconomic state variables for the conduct of monetary policy.
Keywords: G24; E50; 330; Credit crisis; monetary policy; Kreditmarkt; Gesamtwirtschaftliche Liquidität; Geldpolitik; Finanzmarktkrise; USA